2019
DOI: 10.1002/mana.201700398
|View full text |Cite
|
Sign up to set email alerts
|

The concentration behavior of ground state solutions for a critical fractional Schrödinger–Poisson system

Abstract: In this paper, we study the following critical fractional Schrödinger–Poisson system trueright115.20007pt{ε2s(−Δ)su+Vfalse(xfalse)u+ϕu=Pfalse(xfalse)ffalse(ufalse)+Qfalse(xfalse)|u|2s∗−2u,indouble-struckR3,ε2t(−Δ)tϕ=u2,indouble-struckR3,where ε>0 is a small parameter, s∈(34,1),t∈false(0,1false) and 2s+2t>3, 2s∗:=63−2s is the fractional critical exponent for 3‐dimension, Vfalse(xfalse)∈C(double-struckR3) has a positive global minimum, and Pfalse(xfalse),Qfalse(xfalse)∈C(double-struckR3) are positive and have gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In [7], the authors found new concentration phenomena for Dirac equations with competing potentials and subcritical or critical nonlinearities, respectively. See also [8,31,32] for other related results.…”
Section: Introduction and Main Resultsmentioning
confidence: 98%
“…In [7], the authors found new concentration phenomena for Dirac equations with competing potentials and subcritical or critical nonlinearities, respectively. See also [8,31,32] for other related results.…”
Section: Introduction and Main Resultsmentioning
confidence: 98%
“…By the monotone trick, concentration-compactness principe and a global compactness lemma he establishes the existence of ground state solutions. For other existence results we refer to [13,19,25,26,27,29,35,36,37,39] and the references therein.…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…In this case, V and Q all want to attract solutions to their local extreme point, the we call it local competing potential functions. In fact, if the condition is global, there have been some results for Schrödinger-Poisson system [34,35,38] and fractional Schrödinger-Poisson system [40,43].…”
Section: Some Open Questionsmentioning
confidence: 99%